Soybean off-season management practices: impacts on physical and chemical soil properties and crop yield - Lopes dos Santos, Esmael; Ribeiro, Ricardo Henrique; Ribeiro, Ricardo Henrique; Ramalho, Bruna; Bratti, Felipe; Alievi, Cleonei; Debiasi, Henrique (Revista Ceres, 2023)
Off-season crops diversification and gypsum under minimal tillage can improve soil fertility and reduce soil compaction. The objective of this work was to evaluate changes on soil physical and chemical properties and soybean yield grown over off-season crops in combination with gypsum and chiseling. Treatments consisted of gypsum application (0 and 3,5 t ha-1), two tillage systems (no tillage [NT] and minimal tillage [MT] with chiseling) and four soybean off-season crop successions: maize (M); maize+brachiaria (M+B); millet+crotalaria/wheat (Mi+C/W) and maize+black oats (M+O). Gypsum application reduced resistance to penetration (PR) by 12% in M+B system (1.12 kPa), when compared to the same treatment without gypsum. Gypsum increased surface soil Ca contents, mainly in M/O (from 3.81 to 5.66 cmolc dm-3). MT decreased PR in M+B, Mi+C/W and M/O, from 1.28 kPa in NT to 0.98 kPa. MT lowered total soil porosity from 66.9 to 63.1%, but reduced Ca contents compared to NT. Cultivation of crotalaria in the off-season reduced Al levels on the soil surface and grasses increased K and P in depth. Despite the improvements in the soil properties, crop rotations, chiseling and gypsum were not able to increase soybean yields in this 18-month experiment, averaging 3904 kg ha-1.